2015
DOI: 10.2217/fmb.14.119
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cholesterol in Campylobacter jejuni Cytolethal Distending Toxin-Induced Pathogenesis

Abstract: Our findings demonstrate a molecular link between Campylobacter jejuni CDT and cholesterol, which is crucial to facilitate CDT-induced pathogenesis in hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…It should be pointed out that in a more recent study in which Cdts from different microbial species were studied simultaneously, toxin-host interactions were shown not to depend upon fucosylated structures as well as N- and O-glycans (Eshraghi et al, 2010). These authors did, however, observe that several Cdts, including toxin prepared from A. actinomycetemcomitans, C. jejuni , and H. ducreyi , utilized membrane cholesterol; these results corroborated the findings of several other investigators (Guerra et al, 2005; Boesze-Battaglia et al, 2009; Zhou et al, 2012; Lai et al, 2013, 2015). …”
Section: Cdt Subunit Structure and Functionsupporting
confidence: 78%
“…It should be pointed out that in a more recent study in which Cdts from different microbial species were studied simultaneously, toxin-host interactions were shown not to depend upon fucosylated structures as well as N- and O-glycans (Eshraghi et al, 2010). These authors did, however, observe that several Cdts, including toxin prepared from A. actinomycetemcomitans, C. jejuni , and H. ducreyi , utilized membrane cholesterol; these results corroborated the findings of several other investigators (Guerra et al, 2005; Boesze-Battaglia et al, 2009; Zhou et al, 2012; Lai et al, 2013, 2015). …”
Section: Cdt Subunit Structure and Functionsupporting
confidence: 78%
“…In particular, cholesterol plays a crucial role in H. pylori cell invasion and virulence (Lai et al, 2013). Depletion of cellular cholesterol not only attenuates H. pylori -induced pathogenesis (Hutton et al, 2010; Lai et al, 2011) but also promotes autophagy (Cheng et al, 2006), which has been shown to contribute to immune defense against invading pathogens (Levine et al, 2011; Deretic et al, 2013; Lai et al, 2015). Statins, inhibitors of HMG-CoA reductase that are widely prescribed for lowering serum cholesterol, have also been employed to reduce the risk of certain bacterial infections (Chow et al, 2010; Nseir et al, 2010; Boyd et al, 2012; Motzkus-Feagans et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue specimens from mice were formalin-fixed then subjected to IHC staining as described previously [27,34]. Briefly, the tissue sections were de-waxed and rehydrated.…”
Section: Methodsmentioning
confidence: 99%